La ficción biográfica entre Francia, Argentina e Italia (Schwob, Borges, Wilcock, Tabucchi) (El Hilo de la Fabula, 2018)
The new departure introduced by Marcel Schwob’s Vies Imaginaires in the genre of biography did not fail to attract Jorge Luis Borges whose influence in its turn was paramount with writers such as Juan Rodolfo Wilcock and Antonio Tabucchi. This article examines how these four writers produce their biofictions emphasising their poetics and the relationship they develop with their readers.
Keywords: Life–writing; Fictionality; Lives of Infamous Men